Food Safety in the Protection of the Right to Consumer: Access to International Law and Vietnamese Law - Thuong, Nguyen Thi Hoai; Nguyen, Thuong (University of Jember, 2024)
This right to safe food is one of consumers' most important fundamental rights. This issue is directly related to human health and life, the preservation and development of the human race, and the process of international development and integration. Ensuring food safety is currently a topic that has been paid attention to internationally as well as nationally. On a global scale, food safety issues are a significant concern addressed by the world community through many signed international agreements and conventions on ensuring food hygiene and safety. In Vietnam, food safety is one of the most urgent issues in the context of economic development and world integration, which garners concern from the whole society. Although the Vietnamese government has gradually improved the legal system regulating food safety, the situation regarding violations of food safety laws is still quite complicated. The article addresses the need to ensure the right to food safety to consumers, and analyzes the provisions of international and Vietnamese law on this right. From there, recommendations are proposed to countries to improve efficiency in ensuring food safety for consumers.KEYWORDS: Food safety, Right to use safe food, International law, Vietnamese law.